2023
DOI: 10.14202/ijoh.2023.32-42
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the One Health approach in controlling rabies in Minahasa R egency, Indonesia

Abstract: Background and Aim: Minahasa Regency is one of the regions in Indonesia where rabies is endemic. Therefore, this study aimed to explore the implementation and the challenges of the One Health approach in the rabies control program in Minahasa Regency. Materials and Methods: This qualitative study was carried out using semi-structured interviews involving 8 respondents who were stakeholders from five related sectors. A triangulation of source and method was conducted. Results: The results showed that the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…However, multisectoral coordination is still a challenge for many countries, as highlighted in studies conducted by different countries around the world on how countries fail to integrate and translate policies into action, for example, in the Middle East [24], Kenya [26], Qatar [28], the Sub-Saharan region [35], Nigeria [36], South Africa [38], Indonesia [39], Western Asia [40], and China [41]. Reviewed articles n = 23 (50%) indicated that policies, guidelines, and plans need to be integrated to facilitate the implementation of OH activities and multisectoral coordination and collaboration.…”
Section: Challenges In Multisectoral Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multisectoral coordination is still a challenge for many countries, as highlighted in studies conducted by different countries around the world on how countries fail to integrate and translate policies into action, for example, in the Middle East [24], Kenya [26], Qatar [28], the Sub-Saharan region [35], Nigeria [36], South Africa [38], Indonesia [39], Western Asia [40], and China [41]. Reviewed articles n = 23 (50%) indicated that policies, guidelines, and plans need to be integrated to facilitate the implementation of OH activities and multisectoral coordination and collaboration.…”
Section: Challenges In Multisectoral Coordinationmentioning
confidence: 99%
“…The public health sector may differ from the animal sector in terms of its impact on productivity, social economy, politics, and trade [21]. Diverse sector priorities and inadequate allocation of finances and resources to key OH implementation sectors hinder effective cooperation and operationalization of OH [1,39].…”
Section: Challenges In Multisectoral Coordinationmentioning
confidence: 99%